Pembangunan Aplikasi Perangkat Bergerak Program KB Berbasis Android Dengan Menerapkan User Centered Design - Lia Rosalina; Adam Hendra Brata; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Birth control program is a government program to fulfill the quality of reproductive health needs for society. By planning birth control, it can reduces the amount of death of mothers and children as well as minimize the amount of pregnancy to make high quality of small family. From many factor which affect the failure of birth control, the main factor is human resources itself, because many women who are in fertile age did not know that birth control should be done on time. Forget and unwillingnes to ask the nurse about birth control become the background for researcher to develop application of birth control program using android. Data from statista.com shows that there are 75% smartphone users with android OS until the end of 2017. From this background, researcher develops birth control application using User Centered Design method by analyzing from users experiences. So this application has usability value. From the result of usabilty testing using Task Scenario method and Use questionnaire, it shows that 100% for Task Scenario model and 96,20% for Use Questionnaire. From those tests, it shows that the success level of the application is in very good category.